SYSTEM AND METHOD FOR COMPUTER SECURITY AUGMENTED DATA SET ALGORITHM TRAINING (2023)
A method, apparatus and system for data augmentation include receiving a first plurality of binary files each having a first binary structure and including one or more known files containing malicious content and one or more known files not containing malicious content, altering a source code of each of the first plurality of binary files to produce a second plurality of binary files each having a second binary structure that is different from the first binary structure, wherein each altered binary file is functionality similar to the corresponding file in the first plurality of binary files from which it was produced, using the first and second plurality of binary files to train the AM machine learning model to distinguish between binary files containing malicious content and binary files not containing malicious content, and applying the trained AM machine learning model to identify unknown binary files containing malicious content.